Mute Swan weights in relation to breeding - Reynolds, C M (Wildfowl, 1972)
This paper analyses 947 Mute Swan Cygnus olor weights, obtained in the Upper Thames valley, with respect to age, sex and season. It was shown for third year or older swans that weights of 10.6 kg. for males and 8.8 kg. for females divided the heavier nesting and territorial birds from the lighter non-breeders. There is a high (negative) correlation between the clutch size and the date of laying of the first egg. The regression line for clutch size on date has a gradient of -1/10 eggs per day, for 120 first clutches (4-11 eggs) started from 15th March to early May. First-time nesting females tended to lay later than previous nesters, and thus had smaller clutches. About 70% of cygnets hatched were reared from early broods (started in March) compared with about 55% from later broods. Females increased their weight by up to at least 2 kg. just before laying. A theoretical model is put forward relating the female's weight, date of laying and the clutch size.